EFL Students’ Perceptions of AI-Supported Academic Writing: Benefits, Learning Risks, Ethical Issues, and Fairness - Meiristiani, Noeris; Agustia Nindya, Meyga (Jurnal Bahasa Inggris, 2025)
The rapid development of artificial intelligence (AI) has begun to influence academic writing practices, particularly among English as a Foreign Language (EFL) students in higher education. This study investigated Indonesian EFL students’ perceptions of AI use in academic writing, focusing on perceived benefits, learning risks, ethical awareness, fairness concerns, and recommendations for lecturers. Data were collected through a structured questionnaire containing both close-ended and open-ended items, and responses were analyzed using descriptive statistics and thematic analysis. The results show that students generally view AI tools as helpful for improving clarity, vocabulary, and writing confidence, while also acknowledging risks related to overreliance, reduced critical thinking, and the potential for plagiarism. Students demonstrated considerable ethical awareness but expressed concerns about biased AI detectors, unclear institutional policies, and fairness in assessment. They also recommended that lecturers provide clear guidelines on acceptable AI use, balance AI-assisted tasks with manual writing, and apply consistent monitoring practices to maintain academic integrity. Overall, the findings highlight the need for balanced instructional strategies and explicit policy frameworks to ensure responsible and equitable use of AI in EFL academic writing contexts.